2022
DOI: 10.1111/cch.12999
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID‐19 virus outbreak on 24‐h movement behaviours among children in Saudi Arabia: A cross‐sectional survey

Abstract: Background In March 2020, the World Health Organization (WHO) declared the coronavirus (COVID‐19) outbreak as a pandemic. This led many governments to place restrictions on population movement to aid in pandemic control. These restrictions were expected to produce some type of impact on the daily lives of children and their families. The purpose of this study was to investigate the impact of COVID‐19 on 24‐h movement behaviours among Saudi children aged 6–12 years, during the pandemic. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
1
3
2
Order By: Relevance
“…The results of this study also showed that during the pandemic 100% of children in this study exceeded the Saudi sedentary guidelines. This proportion is higher than that recently reported in a parent-based survey study [ 12 ]. Previous data showed that, during the pandemic, approximately 85% of Saudi children exceeded the recommended amount (<2 h/day) of sedentary time [ 12 ].…”
Section: Discussioncontrasting
confidence: 69%
See 4 more Smart Citations
“…The results of this study also showed that during the pandemic 100% of children in this study exceeded the Saudi sedentary guidelines. This proportion is higher than that recently reported in a parent-based survey study [ 12 ]. Previous data showed that, during the pandemic, approximately 85% of Saudi children exceeded the recommended amount (<2 h/day) of sedentary time [ 12 ].…”
Section: Discussioncontrasting
confidence: 69%
“…This proportion is higher than that recently reported in a parent-based survey study [ 12 ]. Previous data showed that, during the pandemic, approximately 85% of Saudi children exceeded the recommended amount (<2 h/day) of sedentary time [ 12 ]. The higher proportion of children that exceeded the sedentary recommendation in our study can be attributed to many reasons.…”
Section: Discussioncontrasting
confidence: 69%
See 3 more Smart Citations